Portrait Implementation Muzara’ah Contract Effort Encourage Improvement Community's Economy - Ishak, Ishak; Saepul, Saepul; Sabani, Akbar (Universitas Alma Ata, 2023)
The purpose of this study is to describe how the process of implementing profit sharing is carried out by agricultural communities in the District. District Anggeraja. Enrekang and whether the profit-sharing model is following the muzara’ah contract in Islam. There are three main topics discussed in this article, namely (1) The potential for shallot farming (2) The mechanism for implementing the muzara’ah contract in shallot farming (3) The economic impact on the community from shallot farming. This type of research uses qualitative methods which are described descriptively. Sources of research data using primary data and secondary data. To obtain valid data, the authors use data collection methods utilizing observation, interviews, and documentation. The data analysis technique used in this research is data reduction, presenting data, and drawing conclusions. The findings of the results in the study indicate that the concept of profit sharing is carried out by the people of Kec. Anggeraja Kab. Enrekang is called by the term bagessele' which is carried out based on the customs of the local community, namely an agreement between the owner of capital and sharecroppers in the form of an oral statement. In the process of implementing shallot farming profit sharing, all the results obtained from agriculture are totaled as a whole, then reduced by the capital that has been issued, and then divided based on the proportion between sharecroppers and capital owners. The mechanism for implementing the profit sharing used is also following the principles of Islamic law in Ramallah because it refers to the pillars and conditions that have been fulfilled. The distribution of ratios also follows the proportion of profit sharing in the muzara’ah contract, namely ½, 1/3, and ¼ following the mutual agreement.